Progressive Muscle Relaxation Dalam Menurunkan Nyeri - Fitriani Fitriani; Kadek Ayu Erika; Syahrul Syahrul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background: pain is a subjective response felt by an individual that caused by several conditions such as surgery or trauma, or due to disease process. pain management is needed to overcome such things as progressive muscle relaxation (PMR) techniques that can reduce anxiety and depression, improve sleep quality, reduce fatigue and reduce pain. Aims of this literature study was to evaluate the effect of progressive muscle relaxation (PMR) in reducing pain levels.Methods: The data base used in this review literature is Pubmed, Science, Direct and google scholarResults : Literature search from 42 articles obtained 5 articles that met the criteria. This study observe the effect of progressive muscle relaxation (PMR) on the level of pain. Some results shows progressive muscle relaxation (PMR) effectively decreases pain levels.Conclusion: progressive muscle relaxation (PMR) is effective in reducing acute pain and chronic pain.Keywords : progressive muscle relaxation, pain